Rancangan Sistem Pengukuran Kinerja Berbasis Human Resource Scorecard Pada Universitas Muhammadiyah Luwuk - Nurhaeda Abbas; Anggraini Sukmawati; Muhammad Syamsun (Jurnal Manajemen dan Organisasi, 2019)
Today the performance measurement of Muhammadiyah Luwuk uUniversity’s performance has not formulated yet based on University’s vision and mission. It will affect the strategic steps needed and performance improvement efforts in the future. Human resource scorecard is the right system to be applied in Muhammadiyah Luwuk University. The purpose of this study is to designed a performance measurement system at Muhammadiyah Luwuk University using the Human Resource Scorecard with four perspectives: stakeholder, academic management and kemuhammadiyaan, operational and innovation, as well as and learning. Data was analyzed by analytical hierarchy process method. This research was conducted by distributing questionnaires, focus group discussions and in-depth interview with stakeholders at Muhammadiyah Luwuk University. The results showed that there were 14 strategic objectives and 33 key performance indicators to be achieved by the priority objectives, which are: empowerment and development of faculty, increased administrative process quality, improved sound budget performance and, improvement of the relationship with stakeholders.